Facultad de Ciencias de la Educación de UNIFE: 50 años formando maestras íntegras - Aliaga Murray, Nelly (2012)
The present article focuses on a brief historical account of thewomen education in the world, of how the lack of educationalopportunities kept the women away for centuries, the worldintellectual scene. This and other situations occurred throughhistory, justifies the creation of an exclusive university forwomen. The Education School of “Universidad Femenina delSagrado Corazón”, since its creation, 50 years ago, was orientedat training professional educators, genuine people, formed witha humanistic base, centered on Christian moral values.